High prevalence of genetic variants previously associated with Brugada syndrome in new exome data. (11th March 2013) - Risgaard, B; Jabbari, R; Refsgaard, L; Holst, AG; Haunsø, S; Sadjadieh, A; Winkel, BG; Olesen, MS; Tfelt‐Hansen, J
<x xml:space="preserve">Abstract</x> More than 300 variants in 12 genes have been associated with Brugada syndrome (BrS) which has a prevalence ranging between 1:2000 and 1:100, 000. Until recently, there has been little knowledge regarding the distribution of genetic variations in the general population. This problem was partly solved, when exome data from the NHLI GO Exome Sequencing Project (ESP) was published. In this study, we aimed to report the prevalence of previously BrS‐associated variants in the ESP population. We performed a search in ESP for variants previously associated with BrS. In addition, four variants in ESP were genotyped in a second Danish control population (n = 536) with available electrocardiograms. In ESP, we identified 38 of 355 (10%) variants, distributed on 272 heterozygote carriers and two homozygote carriers. The genes investigated were on average screened in 6258 individuals. This corresponds to a surprisingly high genotype prevalence of 1:23 (274:6258). Genotyping the four common ESP‐derived variants CACNA2D1 S709N, SCN5A F2004L, CACNB2 S143F, and CACNB2 T450I in the Danish controls, we found a genotype prevalence comparable with that found in ESP. We suggest that exome data are used in research, as an additive tool to predict the pathogenicity of variants in patients suspected for BrS.